1998
DOI: 10.1074/jbc.273.23.14077
|View full text |Cite
|
Sign up to set email alerts
|

The vacB Gene Required for Virulence inShigella flexneri and Escherichia coli Encodes the Exoribonuclease RNase R

Abstract: vacB, a gene previously shown to be required for expression of virulence in Shigella and enteroinvasive Escherichia coli, has been found to encode the 3-5 exoribonuclease, RNase R. Thus, cloning of E. coli vacB led to overexpression of RNase R activity, and partial deletion or interruption of the cloned gene abolished this overexpression. Interruption of the chromosomal copy of vacB eliminated endogenous RNase R activity; however, the absence of RNase R by itself had no effect on cell growth. In contrast, cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
155
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 155 publications
(159 citation statements)
references
References 14 publications
3
155
1
Order By: Relevance
“…In a transposon mutagenesis screen, a Shigella flexneri was isolated that displayed reduced host cell invasion. The disruption was mapped to a locus that was later identified as the gene (vacB/rnr) encoding RNaseR (27,28). More pertinent to this study and as mentioned in the introduction, a pnp mutant of Salmonella enterica was found to have a disregulated TTSS (12).…”
Section: Discussionmentioning
confidence: 99%
“…In a transposon mutagenesis screen, a Shigella flexneri was isolated that displayed reduced host cell invasion. The disruption was mapped to a locus that was later identified as the gene (vacB/rnr) encoding RNaseR (27,28). More pertinent to this study and as mentioned in the introduction, a pnp mutant of Salmonella enterica was found to have a disregulated TTSS (12).…”
Section: Discussionmentioning
confidence: 99%
“…RNase R has been purified to homogeneity and been shown to be a 3Ј to 5Ј exoribonuclease (8). The rnr gene encoding RNase R was identified and shown to be identical to the vacB gene required for virulence in Shigella and enteroinvasive E. coli (9). Efforts to construct mutant strains deficient in RNase R, alone or in combination with other exoribonucleases, showed that RNase R Ϫ single mutant strains are essentially normal, as are multiple mutant strains lacking RNases R and T, RNases R and PH, or RNases R, II, D, and BN (9).…”
mentioning
confidence: 99%
“…Efforts to construct mutant strains deficient in RNase R, alone or in combination with other exoribonucleases, showed that RNase R Ϫ single mutant strains are essentially normal, as are multiple mutant strains lacking RNases R and T, RNases R and PH, or RNases R, II, D, and BN (9). However, a mutant strain lacking both RNase R and PNPase activities could not be made (9), suggesting that such cells are inviable and that the two exoribonucleases might overlap in some important function that had not yet been identified.…”
mentioning
confidence: 99%
“…The rnr gene, which encodes a 5′-3′ exoribonuclease, was originally identified as the vacB gene by Tn5 mutagenesis in Shigella flexneri based on reduced invasion (8,37). In E. coli RNase R is believed to function along with a polynucleotide phosphorylase in the maintenance of ribosomal RNA quality control through the removal of defective RNAs (7).…”
Section: Discussionmentioning
confidence: 99%
“…RNase R is not essential to viability, although inactivation of both the rnr and polynucleotide phosphorylase genes results in bacterial cell death (7). Further, the loss of RNase R activity in E. coli is not evident in the presence of RNase II activity (8). To our knowledge, exoribonuclease activity has not been studied in fusobacteria, and we have not detected any alteration in exoribonuclease activity in the F. nucleatum rnr mutant in comparison to the parental wild type strain (data not shown).…”
Section: Discussionmentioning
confidence: 99%